Legal Pluralism and Marriage Dynamics in the Migrant Community in Port Numbay: Between Tradition, Law, and Contemporary Social Reality - Eko Siswanto; Siti Qamariah Tiflen; Bilaly Sangare (Legitima : Jurnal Hukum Keluarga Islam, 2025)
Purpose - This study aims to reveal the dynamics of marriage among migrant communities in Port Numbay (Jayapura) using a legal pluralism framework to analyze the interaction between tradition, legal provisions, and contemporary social realities in marriage practices. Migration to Papua has formed a new social configuration that displays differences in marriage norms and potential friction with local culture Method – A qualitative approach was used in this study, with research data obtained from observations and interviews with religious leaders, traditional leaders, academics, and legal practitioners. Data analysis was conducted using descriptive analysis methods within a legal pluralism framework. Findings – The main findings of this study show that the marriage practices of the migrant community in Port Numbay take place in various patterns, including marriages between members of the same ethnic group, between different ethnic groups, and mixed marriages with the local community. The problem of migrant marriages is the result of a complex interaction between socioeconomic pressures and legal pluralism, where state law, Islamic law, and local customary law operate simultaneously but are not yet effectively integrated. These tensions place couples, especially women, in a vulnerable position, requiring an approach based on legal pluralism and maqāṣid al-sharīʿah to strengthen contextual protection, justice, and resilience. Research implications – Legal awareness and the harmonization of customary norms with state regulations in marriage practices among migrant communities must be strengthened. Originality/value – This study highlights the unique dynamics of migrant marriages in the multicultural context of Port Numbay.